Characterization of a New M13 Metallopeptidase from Deep-Sea Shewanella sp. E525-6 and Mechanistic Insight into Its Catalysis - Yang, Jin-Yu; Wang, Peng; Li, Chun-Yang; Dong, Sheng; Song, Xiao-Yan; Zhang, Xi-Ying; Xie, Bin-Bin; Zhou, Bai-Cheng; Zhang, Yu-Zhong; Chen, Xiu-Lan (Frontiers in Microbiology, 2016)
Bacterial extracellular peptidases are important for bacterial nutrition and organic nitrogen degradation in the ocean. While many peptidases of the M13 family from terrestrial animals and bacteria are studied, there has been no report on M13 peptidases from marine bacteria. Here, we characterized an M13 peptidase, PepS, from the deep-sea sedimentary strain Shewanella sp. E525-6, and investigated its substrate specificity and catalytic mechanism. The gene pepS cloned from strain E525-6 contains 2085 bp and encodes an M13 metallopeptidase. PepS was expressed in Escherichia coli and purified. Among the characterized M13 peptidases, PepS shares the highest sequence identity (47%) with Zmp1 from Mycobacterium tuberculosis, indicating that PepS is a new member of the M13 family. PepS had the highest activity at 30°C and pH 8.0. It retained 15% activity at 0°C. Its half life at 40°C was only 4 min. These properties indicate that PepS is a cold-adapted enzyme. The smallest substrate for PepS is pentapeptide, and it is probably unable to cleave peptides of more than 30 residues. PepS prefers to hydrolyze peptide bonds with P1’ hydrophobic residues. Structural and mutational analyses suggested that His531, His535 and Glu592 coordinate the catalytic zinc ion in PepS, Glu532 acts as a nucleophile, and His654 is probably involved in the transition state stabilization. Asp538 and Asp596 can stablize the orientations of His531 and His535, and Arg660 can stablize the orientation of Asp596. These results help in understanding marine bacterial peptidases and organic nitrogen degradation.